as raízes da equação
Soluções para a tarefa
Respondido por
2
As raízes da equação
ax² + bx + c = 0
6x² + x - 1 = 0
a = 6
b = 1
c = - 1
Δ = b² - 4ac
Δ = (1)² - 4(6)(-1)
Δ = (1x1) (-)(-)24
Δ = 1 + 24
Δ = 25 ------------------------------------------> √Δ = 5 porque √25 = 5
se
Δ > 0 ( DUAS raízes diferentes)
(baskara)
- b + √Δ
x = ------------------
2a
- 1 + √25
x' = -------------------
2(6)
- 1 + 5
x' = ----------------
12
4
x' = ---------------(divide AMBOS(dois) por 4))
12
1
x' = ------
3
e
- 1 - √25
x" = ---------------
2(6)
- 1 - 5
x" = --------------
12
- 6
x" = --------------( divide AMBOS (dois) por 6 )
12
1
x" = - --------
2
assim
x' = 1/3
x" = - 1/2
pabloousadiaaa:
vlw mano obrigado
Perguntas interessantes
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Geografia,
9 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás